1958
DOI: 10.1128/aem.6.2.97-104.1958
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microbiological Methods Used for the Examination of Precooked Frozen Foods12

Abstract: This paper reports research undertaken by the Quarterrnaster Food and Container Institute for the Armed Forces and has been assignied No. 631 in the series of papers approved for publication. The views or conclusions conitained in this report are those of the authors. They are not, to be construed as necessarily reflecting the views or indorsement of the Department of Defense. 2 Presented at the 56th General Meeting of the Society of American Bacteriologists held in HIouston, Texas, April 29 to May 3, 1956.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
14
0

Year Published

1961
1961
1980
1980

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 7 publications
4
14
0
Order By: Relevance
“…The findings that all of the vegetable samples examined (Table 4) yielded streptococci other than enterococci that could grow in EVA broth is in variance with the results obtained with precooked foods by workers such as Zaborowski et al (1958), who reported this medium to be specific for enterococci. This difference might be explained on the basis of a quantitative difference in the types of streptococci contaminating the two classes of foods.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The findings that all of the vegetable samples examined (Table 4) yielded streptococci other than enterococci that could grow in EVA broth is in variance with the results obtained with precooked foods by workers such as Zaborowski et al (1958), who reported this medium to be specific for enterococci. This difference might be explained on the basis of a quantitative difference in the types of streptococci contaminating the two classes of foods.…”
Section: Discussionsupporting
confidence: 54%
“…The suitability of the various media for determining the MPN of enterococci in precooked frozen foods has been evaluated by Zaborowski, Huber, and Rayman (1958), and Fanelli and Ayres (1959). Zaborowski et al (1958) found that azide dextrose (AD) broth as a presumptive medium yielded the highest most probable number of counts. Also they reported 100 % confirma-tion using EVA when one-tenth dilutions of the original samples were inoculated into this medium.…”
mentioning
confidence: 99%
“…The estimation of enterococci as an index of contamination of frozen foods has been advocated in several recent publications Fuller, 1955, 1956;Zaborowski, Huber, and Rayman, 1958;Kereluk and Gunderson, 1959a). The greater resistance shown by these organisms, as compared with E. coli and other coliforms, to heating and freezing processes and to frozen storage has been cited as strong evidence supporting their use for this purpose (Larkin et al, 1955(Larkin et al, , 1956Kereluk and Gunderson, 1959b).…”
mentioning
confidence: 99%
“…A method has been evolved in which a presumptive count is made in azide dextrose (AD) broth or enterococci presumptive (EP) broth and confirmed by the ethyl violet azide (EVA) broth medium of Litsky, Mallman, and Fifield (1953). This method has been shown to provide a rapid and reportedly specific procedure for counting enterococci in foodstuffs (Zaborowski et al, 1958). For differentiation of S. faecalis types from other enterococci, Barnes (1956a) has proposed an agar medium containing 2,3,5-triphenyltetrazolium chloride.…”
mentioning
confidence: 99%
“…The introduction into large scale commerce of frozen precooked foods with all their attendant potential bacteriological hazards has focused attention on the problems of detecting fecal contamination of foods. There is much evidence in the literature that the methods commonly applied for the detection of fecal indicator organisms in water and milk are unsatisfactory when applied to foodstuffs (Larkin, Litsky, and Fuller, 1956;Zaborowski, Huber, and Rayman, 1958; Kereluk and Gunderson, 1959). This is true even in the case of shellfish where such methods have been used for many years (Kelly, 1960).…”
mentioning
confidence: 99%